KONSEP PENGATURAN PENJAMINAN SIMPANAN NASABAH PADA BANK SYARIAH - Danang Wahyu Muhammad; Ahdiana Yuni Lestari (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2015)
Fund Guarantor Institution (LGI) does not yet have Syariah scheme as a distinguishing feature of Sharia-based society fund guarantee. Meanwhile, the existing Government Regulation, that is PP No. 39 Year 2005 about Bank Customer Fund Guarantee based on Sharia Principles, is very simple so that it is not sufficient and does not cover Islamic Banks. Based on the background, the problem formulation in this research is “What is the concept of customer fund guarantee regulation like in Islamic Banks?” The objective of this research is to make a concept about customer fund guarantee regulation in Islamic Banks.The type of this research is juridical normative that is doctrinal, with law and conceptual approach method. As a doctrinal law research, this research will only review legal materials; primary legal materials, secondary legal materials, and non-legal materials. The analysis of this research uses prescriptive method.The conclusion of the research is that in Banking Operation Principles in Indonesia there are two types of banks; conventional and Islamic bank, where both types use different systems. As a consequence, in principle, the institution that guarantees the customer fund should be distinguished. This is based on some considerations :Islamic Banks proscribes bank interest, because of that they do not use bank interest mechanism in its operation, therefore the institution that guarantees its customer fund should not use bank interest mechanism.In its operational systems, Islamic Banks use covenants that have been determined according to Islamic Fiqh, so the institution that guarantees its customer fund should base its operation system to the covenant that is based on Islamic Fiqh. Islamic Banks are limited by what may be done and what may not be done based on Islamic Fiqh, determination, so the institution that guarantees its customer fund should base its operational on the same determination.Therefore, there will be a consistency between Islamic Banks and the institution that guarantees its customer fund in Islamic Banks which at the end will guarantee protection towards the customers who are willing to perform Islamic religious duty in a good and correct way.